Perkawinan Beda Agama di Republik Yaman Perspektif Hukum Islam dan Hukum Positif - Agustar, Armi; Nurcahaya, Nurcahaya (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
Writing this article wants to describe, related to Yemeni legal regulations, namely the marriage of Muslim women in Yemen. Discussing the annulment of marriages for men who adhere to Islam or Muslims who do not marry Muslim women and women of the book in Yemen. As for the women of the People of the Book who can be married to Muslim men in Yemen, it is necessary to elaborate on the permissibility of marrying women who are not Muslim. Yemen itself fully takes the source of law in the text of the Koran where marriage regulations in Yemen between Muslim men and women of the book are permissible and regulated in Yemen's legal laws. On the other hand, interfaith marriages in other regions related to women of the book cannot be found, in Indonesia, for example, interfaith marriages only describe marriages between Muslims and those who are not Muslim or are not Muslim, there is absolutely no mention of women of the book. For this reason, this article wants to elaborate on the explanation regarding women of the People of the Book, amidst the debate whether or not it is permissible to marry women of the People of the Book, Yemen still adheres to the Al-Quran text which allows Muslim men to marry women of the People of the Book until now.